Complement and renal transplantation: from donor to recipient. - Damman, J; Schuurs, T; Ploeg, R; Seelen, M (2008)
Long-term kidney graft survival is affected by different variables including donor condition, ischemia-reperfusion injury, and graft rejection during the transplantation process. The complement system is an important mediator of renal ischemia-reperfusion injury and in rejecting allografts. However, donor complement C3 seems to be crucial in renal transplantation-related injury as renal injury is attenuated in C3 deficient kidney grafts. Interestingly, before ischemia-reperfusion induced C3 expression, C3 is already induced in donors suffering from brain death. Therefore, strategies targeting complement activation in the brain-dead donor may increase graft viability and transplant outcome.